The idea of Europe : from antiquity to the European Union - Pagden, Anthony (Woodrow Wilson Center series., 2002)
This book addresses the question of what it means, and has meant, to be "European," covering the period from Antiquity to the end of the twentieth century. The essays discuss questions of politics, law, religion, culture, literature, and even affectivity in a broad account of how a distinctive European identity has grown over the centuries and its place in the future evolution of the European Union. In the massive literature of European integration, no other book takes such a long historical perspective, and none other deals directly with the question of identity.